IMPLEMENTASI PROGRAM DESA SIAGA AKTIF DI DESA KARYA TANI KECAMATAN KEMPAS KABUPATEN INDRAGIRI HILIR - Rinda Kristiani Kune; Chalid Sahuri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Development of Villages Active Standby is an advanced program and the acceleration of the development of alert village which began in 2006. And the development of Villages Active Standby implemented through community empowerment, which seeks to facilitate the learning process of rural communities and villages in solving health problems. The main objective of the implementation of this program is the establishment of rural communities and urban neighborhoods caring, responsive, and able to recognize, prevent and address the health problems faced independently, so the degree of health improved. The theory used in this research is the theory of Policy Implementation by Riant Nugroho (2003: 158), which explains the meaning of the implementation of the policy in principle is a way for a policy can achieve its objectives. And to implement public policy, then there are two options available measures, which directly implemented in the form of programs or through policy formulation derivatives or derivatives of such public policy. And also use the Theory of Van Meter Van Horn in Winarno (2014: 158-174), which describes factors that affect to assess the implementation of a policy can be measured or assessed on six indicators, namely the presence of basic measures and goals policy, policy resources, communication between the organization and implementation activities, the characteristics of the implementing agencies, economic conditions, social and political tendency implementers (implementors).Based on research conducted by the researchers, it can be concluded Active Standby Program Implementation Village in Desa Karya Tani District of Kempas not run as expected, and has not reached the output end or purpose of these programs. It can be seen from the indicators that researchers use in assessing or measuring the implementation of this program, not entirely as it should be. It can be seen from the liveliness of village forums are still only run two times a year, a cadre of empowerment that is not yet fully understand the duties and responsibilities, the ease of access to services is affected by midwives who do not apply the village, UKBM that have not been fully implemented, the financial support is not maximized from the village authorities and the private sector, there are still 25-30% of rural communities are less understood and less concerned with the program, the village level regulations have not been fully implemented and not specifically explain the content of the regulation, and also coaching PHBs are not maximized.Keywords: Implementation, Program, Active Alert Village.